Pengaruh Pendidikan Kesehatan Perawatan Kaki Diabetik Dengan Metode Demonstrasi Terhadap Kemampuan Merawat Kaki Pada Pasien Diabetes Melitus Di Rsup Dr Soeradji Tirtonegoro Klaten - SETYANINGSIH, RINA SARI DEWI, Arina Maliya, S. Kep. M.Si. Med (2017)
Background. The disease of DM complications often form of stroke, kidney failure, heart, nephropathy, blindness and even had to undergo amputation. The problem of diabetes leg injury in Indonesia to date is still a complex issue, because the mortality rate and the amputation is still high. One of the treatment DM was with education. Research objectives: Find out the influence of health education against diabetic foot treatment with the method of demonstration in diabetics mellitus in was Dr. Soeradji Tirtonegoro Klaten. Research methods: The research was included in this type of research Pre-experimental design approach Intact-Group Comparison. Enginering samples are non probability sampling with technical purposive sampling of as many as 30 respondents. Data analysis techniques using Paried test T test. Results of research: The average level of knowledge prior to health education is 12. 766 and after extension or increased 15,166 better. The ability of people with diabetes mellitus care for leg before given health education the average rating is 4,666. To know the ability of people with diabetes mellitus in taking care of feet after a given health education with an average 8,133. Summary: Statistically by T test Paried that the value of p = 0.001 meaning there is the influence of health education against diabetic foot treatment with demonstration methods can improve the care of diabetic foot as much as 3,466 from before the demonstration.